Pengaruh Pelatihan, Gaji dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT.Indojaya Grafika - Aurelia Tanatha; Teddyansa Halim; Jurisman Simanjorang; Sunday Ade Sitorus; SUNDAY ADE SITORUS (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
PT Indojaya Graphic is one of the companies engaged in printing. The purpose of this study was to examine the Performance Effect of Training, Salary, Work Environment on Employees of PT Indojaya Graphic. This research uses quantitative research methods with quantitative descriptive research types. The nature of this research is descriptive explanation. In this study, the sample used was 65 people. The model with multiple linear regression. The result is that job training has a partial effect on the performance of PT Indojaya Graphic employees. Salary has a partial effect on the performance of employees of PT Indojaya Graphic. The work environment has a partial effect on the performance of PT Indojaya Graphic employees. Job training, salary, work environment have a partial effect on the performance of PT Indojaya Graphic employees. In conclusion, the better level of training , distribution of commensurate salary proportions and a conducive work environment, will improve employee performance results which indirectly affect improving the quality of employee performance. Keywords: Employee Performance, Salary, Training, Work Environment,